Exploration of Students' Problem Solving Ability on Arithmetic Material in a Constructivist Philosophy Perspective Review - Berliani Ardelia Sukowati; Miftachul Hidayati; Auliya Ningrum; Muhammad Noor Kholid (Universitas Muhammadiyah Surakarta, 2025)
This study aims to explore the mathematical problem-solving abilities of male and female students on arithmetic sequence and series material from a constructivist philosophical perspective. The research was motivated by the generally low problem-solving performance of Indonesian students, as reflected in international assessments such as PISA and TIMSS. Employing a qualitative case study design, the research involved two eighth-grade students from SMP Negeri 3 Satu Atap Tawangharjo, each representing a high-achieving male and female student. Data were collected through written tests, interviews, observations, and documentation, and analyzed using an interactive model. Findings reveal that both male and female students achieved all mathematical problem-solving indicators, yet exhibited distinct cognitive patterns. Male students demonstrated logical and spatial strategies but tended to overlook the rechecking stage, while female students showed more verbal, organized, and reflective problem-solving behaviors. From a constructivist perspective, these differences highlight the importance of meaningful, experience-based learning that supports individual knowledge construction.The study suggests that mathematics instruction should integrate varied contextual problems, promote reflective habits, and adopt gender-responsive strategies to enhance students' problem-solving competence. Future research is encouraged to broaden the scope across different topics and student populations.